2012
DOI: 10.1155/2012/953768
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1 Is Not Associated with Coronary Artery Calcification in Type 2 Diabetes: Results from the PREDICT Study

Abstract: Abstract. Objectives:To determine any association between serum paraoxonase-1 (PON1) activity, protein and coding region genetic polymorphisms and coronary artery calcification (CACS) and to determine factors which modulate serum PON1 in type 2 diabetes (T2DM). Methods and results: 589 patients (419 Caucasian, 120 South Asian, 50 other) from the PREDICT Study were investigated. All patients were asymptomatic for coronary disease and had established T2DM. CACS, lipids, lipoproteins, inflammatory markers, insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(66 reference statements)
0
7
1
Order By: Relevance
“…Concordant with the atheroprotective role of ArylE activity, several studies have shown low activity to be associated with increased CAD risk, CAD severity, endothelial dysfunction, worse collateral flow, and adverse cardiovascular outcomes . However, in contrast to this, a few other studies showed high activity to be associated with increased CAD severity, coronary calcification, and increased risk of myocardial infarction, while other studies have not shown any such associations …”
Section: Discussionmentioning
confidence: 93%
“…Concordant with the atheroprotective role of ArylE activity, several studies have shown low activity to be associated with increased CAD risk, CAD severity, endothelial dysfunction, worse collateral flow, and adverse cardiovascular outcomes . However, in contrast to this, a few other studies showed high activity to be associated with increased CAD severity, coronary calcification, and increased risk of myocardial infarction, while other studies have not shown any such associations …”
Section: Discussionmentioning
confidence: 93%
“…Ikeda et al [22] and Mackness et al [23] reported a low PON1 concentration in coronary heart disease patients compared with healthy patients. Also, it has been demonstrated that decreased PON1 activity predicts a higher risk of major adverse cardiac events and that low serum concentrations of PON1 may be an independent predictor of cardiovascular mortality [2226].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a study on 589 patients (419 Caucasian, 120 South Asian, 50 other) to determine factors which modulate serum PON1 in type 2 diabetes, PON1 activity associated negatively with insulin resistance, triglycerides and 55 M allele; and positively with 192R allele. While PON1 concentration associated negatively with Caucasian ethnicity and duration of diabetes, and positively with 192R allele [ 19 ].…”
Section: Discussionmentioning
confidence: 99%